Interspecific root interaction enhances cadmium accumulation in Oryza sativa when intercropping with cadmium accumulator Artemisia argyi - Xin-sheng Chen; Ze Zhang; Xiang-rong Song; Zheng-miao Deng; Chao Xu; Dao-you Huang; Xian-yan Qin (Ecotoxicology and Environmental Safety, 2024)
The contamination of arable land with heavy metals, such as Cd, is a serious concern worldwide. Intercropping with Cd accumulators can be used for efficient safe crop production and phytoremediation of Cd-contaminated soil. However, the effect of intercropping on Cd uptake by main crops and accumulators varies among plant combinations. Rhizosphere interaction may mediate Cd uptake by intercropped plants, but the mechanism is unclear. Thus, in the present study, we aimed to examine the effect of rhizosphere interaction on Cd uptake by intercropping rice (Oryza sativa L.) with mugwort (Artemisia argyi Levl. et Vant.) in Cd-contaminated paddy soil. We grew O. sativa and A. argyi in pots designed to allow different levels of interaction: complete root interaction (no barrier), partial root interaction (nylon mesh barrier), and no root interaction (plastic film barrier). Our results indicated that both complete and partial root interaction increased the shoot and root mass of A. argyi, but did not decrease the shoot, root, and grain mass of O. sativa. Interspecific root interaction significantly increased the Cd content in the shoots, roots, and grains of O. sativa and the shoots of A. argyi. Increased content of total organic acids in the rhizosphere, which increased the content of available Cd, was a possible mechanism of increased Cd uptake in both plants under interspecific root interaction. Our findings demonstrate that an intercropping system can extract more Cd from contaminated soil than a monocropping system of either A. argyi or O. sativa. However, the intercropping system did not facilitate safe crop production because it substantially increased grain Cd content in O. sativa.